HERMENEUTIKA OTORITATIF KHALED M. ABOU EL FADL: METODE KRITIK ATAS PENAFSIRAN OTORITARIANISME DALAM PEMIKIRAN ISLAM - Nasrullah, Nasrullah (Institut Agama Islam Negeri (IAIN) Palu, 2008)
This paper deals with Abou El Fadlâs hermeneutical-authoritative concept. The hermeneutical athouritative emerges as an anti-thesis to all authoritative-interpretative concepts in Islamic thought. The authoritative- interpretative concept established on Godâs name interpretation. This kind of interpretation claims that interpretation is an absolute right, without comropmizing with the interpretation of meaning with values of justice and contemporary issues of humanity, such as gender, jihÃ¢d issue and practice of democracy concept in Moslem countries.Kata Kunci:Â Â Â hermeneutika otoritatif,Â penafsiran otoritarianisme, pemikiran Islam, hukum Islam, jender